Effect of Particle Size on Local Feed Ingredient Flowability - Amal Ichlasul; Salam Anis; Yamin Abdul Alim; Syamsu Jasmal Ahmari (BIO Web of Conferences)
This study aims to determine the flowability of local feed ingredients with different particle sizes. This study on factorial design (3x5) is based on completely randomized design with three replications. The first factor (A) is particle size. The particle size is fine (mesh 26), medium (mesh 12), and coarse (mesh <12). The second factor (B) is local feed ingredients (rice bran, coffee hull, fish meal, coconut meal, and corn cobs). Each feed ingredient was ground using a milling machine with the type RD-85 DI-2S with a 200 kg/hour capacity and a sieve size of 5 mm. Based on variance, it was shown that the treatment of particle size and the interaction between particle size and various local feed ingredients significantly (P<0.01) affect the flowability of feed ingredients. The flowability of coarse ingredients was significantly different compared to medium and fine particle sizes. Fine and medium particle sizes were not significantly different. Thus, the particle size of feed ingredients greatly determines the flowability of various feed ingredients.